2012
DOI: 10.1088/0022-3727/45/4/045101
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of AlGaAs/GaAs tunnel junctions for ultra-high concentration photovoltaics

Abstract: An n++-GaAs/p++-AlGaAs tunnel junction with a peak current density of 10 100 A cm−2 is developed. This device is a tunnel junction for multijunction solar cells, grown lattice-matched on standard GaAs or Ge substrates, with the highest peak current density ever reported. The voltage drop for a current density equivalent to the operation of the multijunction solar cell up to 10 000 suns is below 5 mV. Trap-assisted tunnelling is proposed to be behind this performance, which cannot be justified by simple band-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 12 publications
2
52
0
Order By: Relevance
“…It has been suggested that a GaAs/AlGaAs TJ with Al content of either 10% [10] or 30% [9,11], or AlGaAs/AlGaAs TJs with Al content <20% [9] can provide an acceptable tradeoff between low resistance and transparency. However, equation 1 applies for a homojunction only.…”
Section: Tj Designmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that a GaAs/AlGaAs TJ with Al content of either 10% [10] or 30% [9,11], or AlGaAs/AlGaAs TJs with Al content <20% [9] can provide an acceptable tradeoff between low resistance and transparency. However, equation 1 applies for a homojunction only.…”
Section: Tj Designmentioning
confidence: 99%
“…Also included are the best literature results for a GaAs/GaAs (8630 A/cm 2 ) and Al 0.3 Ga 0.7 As/GaAs (10100 A/cm 2 ) TJ from [11]. A GaAs/GaAs model from [9] was scaled to fit either our GaAs/GaAs result or the best literature result.…”
Section: Tj Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…A metal layer is the simplest and would allow recombination, but metals block light transmission to the lower cell. Epitaxial tunnel junctions have been deposited by molecular beam epitaxy (MBE) [8] and metal organic chemical vapor deposition (MOCVD) [9], and laser ablation have produced Broken Gap Junction (BGJ) devices [10]. The first two approaches deposit epitaxial crystalline films with heavily doped p-and n-type layers which improve intraband tunneling by minimizing the depletion region [11], while laser ablation processing is not widely adopted in industry.…”
Section: Introductionmentioning
confidence: 99%